Prevalence and Associated Risk Factors of Pulmonary Tuberculosis in Diabetic Patients (Academia Journal of Medicine, 2020)
Background: One-third of India’s population is infected with mycobacterium tuberculosis; there are 12 million active tuberculosis cases in India. One person dies of Tuberculosis every minute in India. No other disease has so much sociological, economic and health significance as Tuberculosis has. In 2005 there were an estimated 8.8 million new cases of Tuberculosis worldwide, with 1.9 million of those occurring in India. In India in 2000, there were an estimated 481,573,000 people over the age of 25 years. Among these, 4.3% i.e. around 20,707,639 had diabetes, 19 and 939,064 developed. Subjects and Methods: The study conducted over a period of 2 yrs. Adult patients with diabetes mellitus with pulmonary Tuberculosis were included, while Diabetic patients with extrapulmonary Tuberculosis were excluded from the study. Results: The maximum incidence of pulmonary Tuberculosis was noted above the age of 30yrs were 13(26.0%). The peak incidence was in the age group of 31 – 40 and 41 – 50 yrs. The mean age is 52.62. As Shown in [Figgure 1], the total numbers of males were 64% and females were 36%. The male to female ratio was 2.11:1 As Shown in [Table 3], the distribution of patient according to their occupation noted were Skilled (18%), Unskilled (38%), Business (16%), Service (2%), Housewife (22%), and Student (4%). As shown in [Table 4], the socio-economic status among 50 patients was distributed into: Upper (2%), Upper Middle (22%), Upper lower (32%), Lower (12%), Lower middle (32%), and Lower-middle (32%). Conclusion: Early diagnosis and properly monitored treatment regimen is the only time tested answer to this problem. All diabetics at the initial diagnosis and every year must have an x-ray chest done. All diabetics with abnormal weight loss, unexplained cough, or sudden increase of insulin requirement should have sputum examination and chest x-ray done.
Keywords: Ziehl-Neilsen Stain; Lowenstein –Jensen Medium; Bilateral Opacities; Mortality Rates